Using Scenarios to Explore the Complexity of Student-Faculty Partnership - Woolmer, Cherie; Godbold, Nattalia; Treanor, Isabel; McCray, Natalie; Kupatadze, Ketevan; Felten, Peter; Bovill, Catherine (Teaching and Learning Inquiry, 2023)
In this paper, we present and reflect on using scenarios and role-plays as an effective approach to engaging in the often complicated conversations about student-faculty/staff partnerships, particularly those involving the scholarship of teaching and learning (SoTL). Students as co-developers of pedagogical processes, as well as co-researchers in SoTL, has become an increasingly valued practice in higher education institutions around the world, one that promises to be transformative in its pursuit to break down the traditional hierarchies and establish more democratic and equitable relationships between faculty/staff and students. While there is a growing body of evidence that demonstrates the value of creating spaces and processes to enhance teaching and learning, it can be challenging to know how to develop and implement partnership in SoTL. How do we actually do it? Many of us need guidance for where and how to get started, how to build effective partnerships, how to work through difficulties, how to share our experiences, and how to invite others into this practice. Informed by our own experiences of engaging in pedagogical SoTL partnerships and drawing upon materials developed for a conference workshop we delivered at the 2019 International Society for the Scholarship of Teaching and Learning (ISSOTL) conference, we argue that scenarios and role-plays, when informed by the principles of Scenario Based Learning (SBL), are effective tools that help explore partnership experiences of faculty/staff and students. We offer considerations for how readers can adopt and adapt scenarios in their contexts and invite further research on the ways SBL contributes to SoTL and partnership. Click here to read the corresponding ISSOTL blog post.